Partitioning effect of nitrogen catalyst into polymerizing particles on dispersion reversible chain transfer catalyzed polymerization (dispersion RTCP) of methyl methacrylate in supercritical carbon dioxide and organic solvents1. Issue 5 (27th December 2018) - Okubo, Masayoshi; Kitayama, Yukiya; Taniyama, Tomoya; Liu, Xiang; Zhang, Jianzheng; Shi, Hao
ABSTRACT: Reversible chain transfer catalyzed polymerization (RTCP) in dispersion polymerization system ( dispersion RTCP) of methyl methacrylate (MMA) was performed with N‐iodosuccimide (NIS) as a nitrogen catalyst in supercritical carbon dioxide (scCO2 ). The solubility of NIS in scCO2 can be controlled by tuning the pressure, and this led to promote NIS partitioning into polymerizing particles. As a result, the molecular weight distribution control was successfully improved by decreasing the NIS solubility in the medium by tuning the scCO2 at a low pressure of 20 MPa. On the other hand, at the same NIS concentration, a solution RTCP of MMA in toluene as a homogeneous polymerization system did not proceed with a controlled/living manner. The importance of NIS partitioning into the polymerizing particles was also confirmed in hexane as well as scCO2 medium. From these results, it was clarified that the NIS catalyst partitioning into the polymerizing particles as main polymerization loci is a key factor to control the molecular weight distribution in the dispersion RTCP of MMA in scCO2 . © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2019, 57, 613–620 Abstract : Poly(methyl methacrylate) powder, having narrow molecular weight distribution, was synthesized by dispersion reversible chain transfer catalyzed polymerization ( dispersion RTCP) in supercritical carbon dioxide (scCO2 ). The predominant partitioning of the NIS catalyst into polymerizing particles was a key factor for the synthesis.